Faktor Appropriate Site Development Green Building Rumah Sakit di Palu - Nirmalawati; Kamaludin, Tutang Muhtar; Mallisa, Zet; Ruslan Yunus; Irfandi (Universitas Kristen Indonesia Paulus, 2025)
The study aimed to assess the implementation of Green Building in hospital buildings in Palu City, by conducting evaluations based on the GreenShip Existing Building Version 1.1 and GreenShip New Building Version 1.2 assessment criteria in the appropriate site development and environmental categories. The research method employed a combination of quantitative and qualitative approaches. Data were obtained from interviews with each respondent at three hospitals in Palu City. Data were processed based on responses to the Greenship Existing Building Version 1.1 and Greenship New Building Version 1.2 assessment criteria. The study found that Anutapura Hospital and Undata Hospital received a gold rating, scoring 9 points out of a maximum of 16 points, or 57%. Tadulako University Hospital received a silver rating, with a score of 9 points, or 52%.